Decreased cTnT Levels Heart Failure Patients with Routinely Taking Standard Therapy - Indrawijaya, Yen Yen Ari; Suharjono, Suharjono; Aminuddin, Muhammad; Retnowati, Endang; Rahman, Gilang Mauladi (Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
Extreme physical stressors like thirst increase the risk of non-communicable diseases, especially heart failure (HF). Cardiac patients should ensure adequate supplies of and adherence to medications. They must avoid crowds, perform certain rituals, and report to the nearest health center if symptoms indicate cardiac decompensation. However, in acute or chronic HF with reduced or preserved ejection fraction (EF), elevated cardiac troponin (cTn) levels carry prognostic value for adverse outcomes. A prospective observational study aimed to evaluate levels of cTnT before and after administration of standard therapy and treatment history in hospitalized HF patients. The samples were collected by consecutive sampling and obtained from 30 patients from May-July 2017. The results showed that the number of patients whose cTnT levels decreased by ten patients (30.68 vs. 12.96 pg/ml; p=0.005) increased by 12 patients (31.00 vs. 76.75 pg/ml; p=0.002) and persistent by eight patients (40.70 vs. 42.41 pg/ml; p=0.779). Changes in serum cTnT levels and the clinical condition of the patient, possible to consider the factors of the patient's clinical condition that affect cTnT levels. There was a decrease in levels of cTnT in patients who regularly took medication (10 patients, 29.74 vs. 17.97 pg/ml; p=0.037), while in patients who did not take medication regularly, there was an increase in levels of cTnT (20 patients, 35.35 vs. 60.51 pg/ml; p=0.025). Evaluation of patients' adherence to heart failure therapy has ruled out major risk factors, such as patients with uncontrolled heart disease, to reduce casualties during Hajj.